2006
DOI: 10.1177/107769900608300110
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Print News Photographs of the Casualties of War

Abstract: This investigation examined effect of news photographs of Iraq war casualties on reader emotional response and attitudes about U.S. military presence, and the impact of inoculation pretreatments. Three print news conditions were used: photographs with caption, photographs accompanied by full text, and text. Photographs plus caption elicited greater emotional response and reduced support for continued U.S. presence, although effect sizes were small. A second study revealed that inoculation treatments reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 1 publication
(1 reference statement)
0
65
0
Order By: Relevance
“…The few studies that have examined this issue have solely manipulated the presence or absence of specific visuals, rather than address the level of graphicness in each visual presentation in the United States (see Domke et al, 2002;Pfau et al, 2006;Pfau et al, 2008). The goal of this study is therefore to examine whether varying degrees of graphicness in war visuals lead to differences in war policy beliefs and attitudes.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The few studies that have examined this issue have solely manipulated the presence or absence of specific visuals, rather than address the level of graphicness in each visual presentation in the United States (see Domke et al, 2002;Pfau et al, 2006;Pfau et al, 2008). The goal of this study is therefore to examine whether varying degrees of graphicness in war visuals lead to differences in war policy beliefs and attitudes.…”
mentioning
confidence: 98%
“…Recently, researchers have investigated the impact of visuals on viewer attitudes toward war policies in general (see Ayish, 2001;Domke, Perlmutter, & Spratt, 2002;Pfau et al, 2006;Pfau et al, 2008). Scholars have suggested that the use of graphic visuals may impact positive or negative public sentiments regarding military operations (Pfau et al, 2006).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers have shown that television news stories of combat operations accompanied by visual footage would affect female viewers more. Two studies examining combat news photographs revealed that women were more influenced (Pfau et al, 2006;Thompson, Clarke, & Dinitz, 1974). Research on negative video news also has identified gender differences (Furnham & Gunter, 1985;Gunter, Furnham, & Gietson, 1984).…”
Section: Visual Depictions Of Combat Influence Attitudesmentioning
confidence: 96%
“…Recent studies confirm that the context in which casualties are communicated to American audiences is just as important for understanding the public's assessment of war costs as the fact that losses have occurred. Casualty reports containing images of American dead affect public support more than textual descriptions only (Gartner, 2011;Pfau et al, 2006;Pfau et al, 2008). Americans also seem more sensitive to war deaths when casualty rates are rising rather than when they are falling (Gartner, 2008;Gartner, et al, 1997), and when casualty rates are borne unequally by different segments of society (Kriner & Shen, forthcoming).…”
Section: War Costs and War Supportmentioning
confidence: 99%